Internalizing Global Value Chains: A Firm-Level Analysis - Alfaro, Laura; Antràs, Pol; Chor, Davin; Conconi, Paola (Journal of Political Economy, 2019)
A key decision facing firms is the extent of control to exert over the different stages in their production processes. We develop and test a property rights model of firm boundary choices along the value chain. We construct firm-level measures of the upstreamness of integrated and nonintegrated inputs by combining information on firms’ production activities in more than 100 countries with input-output tables. Whether a firm integrates upstream or downstream suppliers depends crucially on the elasticity of demand it faces. Moreover, integration is shaped by the relative contractibility of stages along the value chain, as well as by the firm’s productivity.